Impacto De La Niif 9 - Instrumentos Financieros En El Proceso Contable De La Empresa Inpaecsa - Merchán Manzano, Carlos Ariel (2019)
The treatment of accounting and financial information becomes increasingly rigorous and systemic, since it is regulated and must be performed in an appropriate manner in accordance with the respective fundamentals of the International Financial Reporting Standards (IFRS) and considering their respective updates . The present investigation carried out in the industrial company INPAECSA of the Babahoyo Canton, whose theme is "Impact of IFRS 9 - Financial Instruments in the accounting process", taking greater emphasis on the effects and changes in the treatment of accounts receivable. The main objective of the research was: Analyze the impact generated by the application of IFRS 9 in the accounting process of the accounts receivable for the commercial period 2018 of the Industrial Papelera Ecuatoriana S.A., of the Babahoyo canton. The implementation of this rule will bring about previous changes in any company, as regards the treatment of accounts receivable and others. The specific objectives are aimed at knowing and identifying the changes of the current IFRS 9 versus the IAS 39, in the treatment of the accounting processes of the accounts receivable of INPAECSA. The methodology used was descriptive and it was considered to obtain the information, the interview application and the collection of information through surveys to a population of 36 people of which 15 people were taken as sample. According to the results of the research, people in the entity are unaware of the changes that the implementation of IFRS 9 would bring with respect to accounts receivable, so they have to look for training programs, but the entity has not generated a training plan for its staff in relation to this issu